Integrated System for Continuous Improvements in the Business Organization - Kuzmanova, Mariyana (Research Papers, 2009)
In the study are considered some important problems of the integrated system for business organization’s continuous improvements, connected with the effectiveness of change management, competitiveness and benchmarking. In this connection the results of the lead pilot research in the effective management of changes’ field are presented. The research is with strategic orientation through which long-term sustainable development of the self-learning organization is stimulated. On the basis of this, these business organization readiness assessments are lead off for continuous improvements benchmarking - results - changes - competitive advantages through the use of flexible system, consisted of competitive standards for assessments of the effectiveness.